The method of forming an individual technique for solving problems of primary school students - Ismanova G.G,; Omonbekova Nozimakhon, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article provides information on the methodology for the formation of an individual technique for solving problems for a primary school student. Learning to solve text problems has always been an important part of the school mathematics course.